Bimbingan Teknis Pemanfaatan Limbah Kulit Kopi sebagai Biofertilizer dalam Mendukung Pertanian Berkelanjutan - May Kurnia Pratiwi; Mochamad Agung Indra Iswara; Wahyuni Ningsih; Shabrina Adani Putri; Cucuk Evi Lusiani; Mufid (PELITA NUSA TENGGARA, 2026)
Coffee husk is a by-product of coffee bean processing that offers substantial potential for conversion into biofertilizer. Despite this potential, limited knowledge and technical skills among small business actors restrict the optimal utilization of this waste, reducing opportunities for value-added product development and contributing to environmental concerns. This study reports on the implementation of Technical Guidance on the Utilization of Coffee Husk as Biofertilizer to Support Sustainable Agriculture, aimed at enhancing participants’ competencies in processing coffee husk through a simple fermentation method. The program comprised theoretical instruction on the benefits and potential of coffee husk, technical training on biofertilizer production, and practical hands-on processing using basic equipment. Results demonstrated significant improvements in participants’ knowledge and skills in transforming coffee husk into biofertilizer. Evaluation surveys indicated that 77% of participants were very satisfied, while 23% were satisfied with the training. The program effectively strengthened technical capabilities, promoted productive utilization of organic waste, and supported sustainable agricultural practices.